Genotype II Live-Attenuated ASFV Vaccine Strains Unable to Completely Protect Pigs against the Emerging Recombinant ASFV Genotype I/II Strain in Vietnam - Nguyen Van Diep; Nguyen Van Duc; Nguyen Thi Ngoc; Vu Xuan Dang; Tran Ngoc Tiep; Viet Dung Nguyen; Thi Tam Than; Dustin Maydaniuk; Kalhari Goonewardene; Aruna Ambagala; Van Phan Le (Vaccines, 2024)
Background: African swine fever virus (ASFV) continues to spread globally, causing severe economic losses to pig farmers. Vietnam licensed two live attenuated vaccines based on the ASFV strains ASFV-G-ΔI177L and ASFV-G-ΔMGF to control the ongoing ASF outbreaks. In 2023, newly emerging highly virulent recombinant ASF viruses (rASFV I/II) containing genetic elements from both p72 genotype I and II ASF viruses were reported from Northern Vietnam. Objective: This study evaluated whether the two vaccine strains were able to protect the pigs against the emerging rASFV I/II strain VNUA/rASFV/TN1/23. Results: Pigs vaccinated with ASFV-G-ΔMGF or ASFV-G-ΔI177L, when challenged with rASFV I/II, succumbed to the infection, or developed signs of chronic ASF. Conclusions: The findings from this study show that both vaccine strains that are licensed and used in Vietnam are unlikely to protect pigs from the emerging highly virulent rASFV I/II. This complicates the ongoing efforts to control ASF in Asia and globally and emphasizes the urgent need for a novel vaccine that can effectively protect pigs from the rASFV I/II.